"I think it was a trick to fail Eastern": A multi-level analysis of teachers' views on the implementation of the SHRP Program in Uganda. (January 2021) - Wenske, Ruth S.; Ssentanda, Medadi E.
Highlights: Teachers doubt SHRP's relevance because they know it is donor-funded. SHRP's top-down structure undermines a holistic approach in Mother Tongue education. Central and eastern regions have a divergent understanding of the SHRP materials. New learner-centered pedagogies are successful when introduced as concrete methods. Teachers' creative combination of teaching methods undermines either/or narratives. Abstract: This article is possibly the first qualitative research on the USAID-funded School Health and Reading Program (SHRP), implemented in Uganda since 2012. The SHRP program is aimed at scaling up the Thematic Curriculum (TC) reform, which was the first attempt to standardize the use of mother tongues in lower primary schools through child-centred pedagogical practices. SHRP has expanded the TC to additional local languages and districts, providing new learning materials – including specific teaching techniques – and teacher training to support it. However, the implementation of SHRP is marked by the fact that it is a donor-led reform that is perceived by teachers as an external intervention not well suited for Ugandan classroom realities. Our research is a multi-layered analysis of how teachers perceive the reform as its grassroots implementers. We ask how SHRP's pedagogical emphasis on child-centred pedagogy is linked to it being donor-funded, and how teachers translate this perceived link into their classroom practices. We trace the links between the policy, classroom, and community levels to make concrete suggestions on how the SHRP program can benefit from teachers' resources and creativity, while highlighting which aspects of mother tongue education the Ugandan Government needs to prioritize on a national level, and which aspects need to be better adjusted on a regional basis.